Konsep Ketenangan Jiwa Menurut Al-Qusyairi - Ema Nurlaila; Nabilla Kartika Sari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The Koran is considered a universal guide for humans until the end of time, emphasizing that a person's glory is not determined by wealth or physical appearance, but rather by the level of piety. The Prophet's hadith also emphasizes that Allah SWT watches over a person's heart and actions, not just his physical condition. A pure soul will produce good deeds, bringing us to a discussion of the soul in the context of psychology. Psychology, as a science that studies human behavior and relationships between humans, finds relevance in the concept of the soul or "nafs" according to the Islamic view. Understanding the concept of mental education from an Islamic perspective is important to gain a deeper understanding of spiritual values ​​and the importance of life.